Anodic oxidation of additively manufactured Sc-doped Al–Mg alloy in aqueous cerium (III) nitrate for corrosion protection - Denise Yin; Plamen A. Demirev; Tanner R. Hamann; David M. Lee; Maddison R. Harman; Michael V. Cyrana; Steven. M. Storck; Charles W. Kerechanin; Rengaswamy Srinivasan (Journal of Materials Science: Materials in Engineering)
Abstract Additively manufactured scandium-doped AA5083 aluminum-magnesium alloy (AA5083-Sc) has a higher yield strength compared to the undoped version. However, AA5083-Sc is prone to pitting and microbiologically induced corrosion in seawater. Chemical conversion coating using aqueous cerium (III) nitrate, Ce(NO3)3, provides only a moderate improvement in corrosion resistance. Electrochemical anodic oxidation of the alloy’s surface in a 0.2-M Ce(NO3)3 solution at pH 4, conducted over an extended period at low current density, significantly enhances its corrosion resistance. After undergoing surface oxidation, the alloy demonstrates corrosion resistance for more than a year when submerged in aerated water containing 3.5% sodium chloride and two types of corrosion-inducing bacteria: Vibrio penaeicida and Thalassospira profundimaris. Electrochemical oxidation transforms the alloy surface oxide from an insulator to a p-type semiconductor, effectively slowing down the cathodic reduction reaction without hindering anodic oxidation. Since the rate of electrochemical corrosion is determined by the slower of two reactions—metal oxidation and the accompanying cathodic reaction—our findings suggest that cathodic reaction slowing is sufficient to reduce the corrosion rate. Additionally, cerium is known for its antifouling properties, and treating the surface with cerium also helps to minimize biofouling and microbial colonies. Graphical Abstract